Accelerated theta-burst transcranial magnetic stimulation of the bilateral dorsolateral prefrontal cortex in a patient with post-traumatic stress disorder and major depressive disorder: Case report - Chang, Chun-Hung; Liu, Chieh-Yu; Chen, Shaw-Ji; Tsai, Hsin-Chi (Frontiers in Psychiatry, 2023)
Background: Theta-burst transcranial magnetic stimulation has demonstrated promising effectiveness as treatment for posttraumatic stress disorder (PTSD) and depression. However, the effect of accelerated theta-burst stimulation (TBS) in comorbid with PTSD and depression remains unknown. Case presentation: We report a case of a 25-year-old woman with PTSD and depression whose symptoms markedly improved after continuous TBS of the right dorsolateral prefrontal cortex (DLPFC) and intermittent TBS (iTBS) over the left DLPFC, and then with 20 min break before the 2nd iTBS session. Conclusions: Accelerated TBS over the bilateral DLPFC may improve severe PTSD and depression. Accelerated TBS may have more improvement of depression symptoms than PTSD symptoms. Further trials are warranted to investigate the effect and safety for patients with complicated PTSD and depression.